Has COVID changed consumer payment behavior? - Claire Greene; Ellen Merry; Joanna Stavins (Federal Reserve Bank of Boston, 2021)
The COVID-19 pandemic has caused large changes in consumer spending, including how people make their payments. We use data from a nationally representative survey of U.S. consumers collected before COVID in 2018 and 2019 and during COVID in 2020 to analyze changes in consumer payment behavior during the pandemic. We find that compared with their payment behavior in 2019, consumers had shifted some of their purchases from in person to online by fall 2020, significantly lowered their use of cash for purchases, and shifted their personto-person (P2P) payments away from paper (cash and checks). Those changes are consistent with what we might expect, as many people were less able or willing to shop in person. The adoption of electronic P2P increased, especially the use of payment apps such as PayPal, Venmo, and Zelle. Consumers who worked exclusively from home during COVID made significantly higher shares of their payments online or through mobile devices and were less likely to use cash at all compared with those who worked at least partly in person, even after we control for income and education levels. In contrast, payment-behavior changes that took place from 2018 to 2019 were smaller in magnitude and largely insignificant, suggesting that COVID likely accelerated any longer-term trends. Although it is too soon to determine whether these changes will persist for the longer term, we observed them several months after the onset of the pandemic, so they certainly were not just temporary shifts.
Keywords: D12; D14; I12; I18; L81; 330; consumer payments; consumer surveys; payment behavior; COVID